Governing uranium globally - Cindy Vestergaard (Danish Institute for International Studies (DIIS), 2015)
The Governing Uranium project is a global research effort studying the implications of a changing uranium market, specifically the production, processing and transport of uranium ore concentrates (UOC), commonly referred to as "yellowcake". In total, 15 uranium producing and consuming countries were studied, representing 85% of global production and 70% of consumption. The concluding final report published 28 August 2015, provides a mapping of an evolving system of treaties, guidelines, and regional and national obligations at a time when the uranium market is shifting both structurally and geopolitically. This regulatory snapshot is particularly relevant as more front-end materials fall under the full-scope safeguards system of the International Atomic Energy Agency (IAEA), placing new obligations on state regulatory authorities and industry and facility operators, as well as new verification responsibilities on the IAEA. This means that, although the three rules of real estate apply to uranium (location, location, location), the uranium market is still global, while export controls and nuclear security are still local (that is, national). The expansion of civilian nuclear fuel cycles to new centres of production and consumption thus calls for increased harmonisation of regulations across states. The report begins with a look at the uranium industry (Chapter 2), followed by descriptions of the evolving application of IAEA safeguards (Chapter 3) and the international nuclear security structure (Chapter 4) as it applies to the (very) front-end of the nuclear fuel cycle. Chapter 5 analyses best practices in tracking and inventory controls to ensure that safeguards and security obligations are met efficiently and effectively. Each chapter provides recommendations for addressing governance gaps at the international and national levels as the industry undergoes legal and structural reforms. It attempts to assist long-time suppliers in updating governance approaches and newcomers in developing nationally appropriate regulatory systems from scratch based on global best practices.
Keywords: 300